2006
DOI: 10.1371/journal.pmed.0030215
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Pig Pancreatic Tissue Transplantation for the Treatment of Diabetes

Abstract: BackgroundTransplantation of embryonic pig pancreatic tissue as a source of insulin has been suggested for the cure of diabetes. However, previous limited clinical trials failed in their attempts to treat diabetic patients by transplantation of advanced gestational age porcine embryonic pancreas. In the present study we examined growth potential, functionality, and immunogenicity of pig embryonic pancreatic tissue harvested at different gestational ages.Methods and FindingsImplantation of embryonic pig pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 64 publications
4
67
1
Order By: Relevance
“…2D). This observation emphasizes the long-term regenerative capability of the pancreatic tissue, in agreement with our previous mouse studies (9).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…2D). This observation emphasizes the long-term regenerative capability of the pancreatic tissue, in agreement with our previous mouse studies (9).…”
Section: Resultssupporting
confidence: 93%
“…Other studies suggested that E28 pancreatic tissue might be accepted in nonimmunosuppressed rats (33) and monkeys (34). In contrast, our mouse (9) and rat (35) data has revealed fierce rejection of pig embryonic tissue of any gestational time point in the absence of immune suppression, while demonstrating that the immunogenicity of E42 tissue was relatively lower compared to tissues harvested at E56 or beyond (9). Therefore, we proposed that mild immune suppression might suffice to permit engraftment and growth of the E42 embryonic tissue.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations